Sweet Wines Produced by an Innovative Winemaking Procedure: Colour, Active Odorants and Sensory Profile - Ruiz, M.J.; Moyano, L.; Zea, L. (South African Journal of Enology and Viticulture, 2016)
The colour, aroma-active compounds and sensory properties of sweet wines from Pedro Ximenez grapes produced by means of an innovative winemaking procedure, based on controlled chamber-drying of grapes, partial fermentation of the must (to 4% or 8% vol ethanol) and subsequent accelerated ageing by contact with oak chips, were studied. Fermentation made the musts less brown and more yellow, whereas ageing made them darker and increased their brown, reddish and yellowish hues. Overall, the musts fermented to 8% vol ethanol exhibited higher odour activity values (OAVs). In addition, the musts aged with oak chips were slightly different from those without chips. Expert tasters gave the highest scores to the musts fermented to 8% (v/v) ethanol with 2 g/L of oak chips added. The winemaking process studied would allow the existing range of sweet wines from dried grapes to be expanded by using a fast, flexible, hygienic procedure.